2021
DOI: 10.7717/peerj.12585
|View full text |Cite
|
Sign up to set email alerts
|

Functions of 1,25-dihydroxy vitamin D3, vitamin D3 receptor and interleukin-22 involved in pathogenesis of gout arthritis through altering metabolic pattern and inflammatory responses

Abstract: Background Gouty arthritis (GA) is a common type of inflammatory arthritis. Recent studies demonstrated that 1,25-dihydroxy vitamin D3 (1,25(OH) 2 VD3) and vitamin D3 receptor (VD-R) play a protective role in acute inflammation, but interleukin-22(IL-22) promotes inflammation, especially for arthritis. However, our understanding of the responses of 1,25(OH) 2VD3 and IL-22 to gout was still unclear. Presently, in-depth metabolomics, bioinformatics and clinical characteristics analyses were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…CYP27B1 enzyme is present in all endocrine cells, such as pancreatic islets and parathyroid, thyroid, testes, ovary, and placental cells [ 44 ], in which calcitriol is synthesized intracellularly; it also modulates hormone release and metabolic functions [ 45 ]. In addition, vitamin D adequacy enhances DNA repair, suppresses malignant cell development [ 46 , 47 , 48 ], and improves the prognosis of malignancies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CYP27B1 enzyme is present in all endocrine cells, such as pancreatic islets and parathyroid, thyroid, testes, ovary, and placental cells [ 44 ], in which calcitriol is synthesized intracellularly; it also modulates hormone release and metabolic functions [ 45 ]. In addition, vitamin D adequacy enhances DNA repair, suppresses malignant cell development [ 46 , 47 , 48 ], and improves the prognosis of malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…Proper vitamin D intake is inversely associated with lung cancer incidence [ 49 ]. Sufficient circulatory D and 25(OH)D concentrations (i.e., above 50 ng/mL) [ 9 ] lead to better physiological responses, such as defense against microbes [ 50 ], the prevention of autoimmune diseases such as multiple sclerosis and inflammatory bowel disease [ 51 , 52 ], and the synthesis and secretion of hormones [ 45 ], controlling the renin-angiotensin-aldosterone system (RAS) and the FGF23/klotho system [ 11 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the remaining 103 studies, 71 studies were removed for reasons including not providing full text, insufficient data, and failure to meet our criteria. Ultimately, we included 33 studies [ 28 , 33 , 34 , 35 , 36 , 37 , 44 , 45 , 46 , 47 , 48 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ] and 3422 participants (2149 gout patients and 1273 healthy controls). The flow diagram for the assessment of studies identified in the systematic review is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“… Forest plot for different metabolites between gout and health. Data from references [ 7 , 28 , 33 , 34 , 35 , 36 , 37 , 44 , 45 , 46 , 47 , 48 , 51 , 52 , 53 , 54 , 55 , 56 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. …”
Section: Figurementioning
confidence: 99%
“…12,13 Additionally, similar to T helper 17 cells, ILC3s produce a variety of distinct cytokines, including interleukin (IL)-17 and IL-22, that are associated with HUA severity and development. 14,15 Nonetheless, the association between HUA and ILC3s remains unclear.…”
Section: Introductionmentioning
confidence: 99%